Curing of chronic hepatitis C combined with coronavirus disease 2019 in a couple over 85 years old: a case series study - Zeng, Qing-Lei; Lv, Xue-Yan; Chen, Ru-Yue; Pan, Ya-Jie (Frontiers in Microbiology, 2024)
Introduction: Data on the management of patients aged more than 85 years with chronic hepatitis C virus (HCV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sequential infections are lacking.The current study described the management of an older couple aged more than 85 years with these above-mentioned two diseases treated with 12 weeks of sofosbuvir/velpatasvir (Epclusa) and 5 days of nirmatrelvir/ritonavir (Paxlovid) sequentially. The effectiveness and safety profiles were closely monitored during therapy and till 9 months posttreatment.In late March 2023, the husband with the main complaint of repeated gingival bleeding and asymptomatic wife were 86 and 85 years old, and had HCV RNA levels of 91,800 and 6,630,000 IU/mL, respectively. On the fourth day of sofosbuvir/velpatasvir treatment, the husband had a moderate headache, and the wife had severe headache and moderate fever and dizziness. We then found that their SARS-CoV-2 test results were positive. After careful consideration, the expert panel decided to treat the couple with oral nirmatrelvir/ritonavir (300 mg/100 mg, twice daily) beginning on the fifth day of sofosbuvir/velpatasvir treatment for 5 days. During the 5 days of nirmatrelvir/ritonavir treatment, the patient's symptoms and signs gradually improved, and the patient was negative for SARS-CoV-2 RNA on the fifth day of nirmatrelvir/ritonavir therapy. Meanwhile, the husband's HCV RNA was not detectable till posttreatment month 9, and his ALT level was normal beginning at week 1 of sofosbuvir/velpatasvir treatment. Moreover, the wife's HCV RNA was not detectable after week 4 of sofosbuvir/velpatasvir treatment till posttreatment month 9. Notably, no other symptoms or signs occurred during the treatment or follow-up period, and other serum biochemical parameters remained stable until 9 months after the discontinuation of sofosbuvir/velpatasvir treatment.The older couple aged more than 85 years with chronic HCV and SARS-CoV-2 sequential infection were safely cured by the sofosbuvir/velpatasvir and nirmatrelvir/ritonavir sequential treatment.Discussion: This study suggested that old age should not be a barrier to HCV/SARS-CoV-2 treatment. Given that the proportion of older HCV-infected patients is increasing, clinical trials of direct-acting antiviral agents should include older HCVinfected individuals.